Vitamin plant derived carbon sodium ion battery negative electrode material and preparation method thereof

By using vascular plant-derived carbon materials, the problems of insufficient sodium storage capacity and first-time Coulomb efficiency of existing sodium ion battery negative electrode materials are solved, and efficient sodium ion transmission and storage are achieved, which is suitable for industrial applications.

CN119481045APending Publication Date: 2025-02-18SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411481527.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The sodium storage capacity and first-time Coulomb efficiency of existing sodium ion battery negative electrode materials are insufficient, and the selection range of biomass precursor materials is limited, making it difficult to meet industrial needs.

Method used

Use vascular plant-derived carbon as the negative electrode material of sodium ion battery, and select plant tissues with dense distribution of vascular bundles with high cellulose content for carbonization to form hard carbon materials with micropores or nanopores, and pass through alkali and acid liquid. The washing step of deionized water removes impurities and improves the electrochemical properties of the material.

Benefits of technology

The sodium storage capacity and first-time coulomb efficiency of hard carbon materials have been significantly improved, reaching 70-90%. Moreover, due to the simple and wide distribution of raw materials, the processing process is simple and easy to operate, and it is easy to achieve industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481045A_ABST
    Figure CN119481045A_ABST
Patent Text Reader

Abstract

The invention relates to a vascular plant derived carbon sodium ion battery negative electrode material and a preparation method thereof. The vascular plant derived carbon sodium ion battery negative electrode material is generated by carbonizing tissues with densely distributed plant vascular bundles; the vascular plant derived carbon sodium ion negative electrode material is provided with micron holes or nano holes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery negative electrode material and a preparation method thereof. Background Art

[0002] With the increasing global demand for renewable energy and the continuous development of electric transportation technology, battery technology has become a research field that has attracted much attention. Traditional lithium-ion batteries have become the most mainstream battery technology at present. However, it also has many problems, such as high cost and uneven resource distribution. Sodium-ion batteries have attracted much attention in recent years due to their advantages such as low cost and abundant resources. They are seen as a battery technology that is expected to replace traditional lithium-ion batteries in the future and become a more excellent and environmentally friendly battery technology.

[0003] At present, the negative electrode material of commercial sodium-ion batteries mainly uses biomass hard carbon. Biomass hard carbon has the characteristics of abundant resources, strong sustainability, low cost and low pollution. Its amorphous carbon structure has a high sodium storage capacity. The sources of biomass hard carbon, which is relatively mature at present, mainly include bamboo, straw, coconut shell, etc., especially coconut shell carbon has been widely used in commercial hard carbon. However, due to the rapid development of the coconut shell carbon industry, coconut shell is also facing the situation of insufficient supply of raw materials.

[0004] Jiang Chunhai et al. used fruit shells as biomass precursors to prepare hard carbon materials for sodium ion batteries in "A waste biomass fruit core derived hard carbon material and its preparation method and application" (China Patent Publication No. CN115863634A). However, the output of fruit cores cannot meet industrial demand in large-scale applications of hard carbon.

[0005] Renewable Energy.189(2022)630-638 reported the role of cellulose in improving the sodium storage capacity of hard carbon and the first coulombic efficiency of hard carbon. However, this requires a high proportion of cellulose in the biomass precursor material, which greatly narrows the selection range of biomass precursor materials. Therefore, it is urgent to provide a biomass hard carbon sodium ion battery negative electrode material with a wide source and simple preparation, which can improve the sodium storage capacity of hard carbon and obtain a higher first coulombic efficiency. Summary of the invention

[0006] In view of the defects of the prior art, the present invention aims to provide a vascular plant-derived carbon sodium ion battery negative electrode material with a wide range of sources and simple preparation, as well as a preparation method thereof. The vascular tissue of the plant contains a high level of cellulose, which can promote the formation of graphite crystallites and closed micropores in hard carbon, increase the sodium storage capacity of hard carbon, and obtain a higher first coulomb efficiency.

[0007] In a first aspect, the present invention provides a vascular plant-derived carbon sodium ion battery negative electrode material, wherein the vascular plant-derived carbon sodium ion battery negative electrode material is generated by carbonization of tissue with densely distributed plant vascular bundles, and the vascular plant-derived carbon sodium ion negative electrode material has micropores or nanopores and has good sodium storage performance.

[0008] The plant vascular tissue used in the present invention is a plant tissue with dense vascular bundles. The part with less vascular bundles is peeled off, and the vascular tissue with higher cellulose content is retained. Cellulose is conducive to the formation of closed micropores in hard carbon, increasing its sodium storage capacity. The vascular bundle has a natural pore structure, and the micropores / nanopores formed are conducive to the transmission of sodium ions in hard carbon.

[0009] Compared with plant fiber materials, the advantages of the plant tissue with denser vascular bundles used in the present invention are uniform distribution, moderate size, and parallel array of straight channels, which are conducive to the infiltration of electrolyte and efficient transmission of sodium ions.

[0010] Preferably, the diameter of the micropore is 1-10 μm; the diameter of the nanopore is 0.1-10 nm.

[0011] Preferably, the vascular plant derived carbon sodium ion negative electrode material has an average conductivity of 25 mA g -1 The current density is 250~400mAh g -1 The reversible capacity of the battery is 70% to 90% for the first time.

[0012] In a second aspect, the present invention also provides a method for preparing a vascular plant derived carbon sodium ion battery negative electrode material, comprising: (1) taking a part of the plant where vascular bundles are densely distributed, and peeling off a part where vascular bundles are less distributed, to obtain a biomass precursor; (2) washing and drying the obtained biomass precursor and then carbonizing it at high temperature in an inert atmosphere to obtain vascular plant-derived carbon; (3) The vascular plant-derived carbon is washed with alkaline solution, acid solution and deionized water respectively, and then dried, ground and sieved to obtain the vascular plant-derived carbon sodium ion negative electrode material.

[0013] Preferably, in step (1), the part where the plant vascular bundles are densely distributed is the epidermis of leaves and stems of monocotyledons or the xylem and phloem of secondary growth of roots and stems of dicotyledons; the monocotyledons are at least one of wheat, corn, ginger flower, rice, leek, onion, daylily, cucumber, garlic, lily, sugarcane, bamboo, orchid, iris, palm tree and cattail; the dicotyledons are at least one of cotton, soybean, peanut, sunflower, sweet potato, potato, apple, tobacco, mint and various melons; preferably, the part where the plant vascular bundles are densely distributed is the epidermis of fully mature cattail leaves, the green part of bamboo or the bark of gymnosperms (ginkgo).

[0014] Preferably, in step (2), the cleaning includes deionized water cleaning and ethanol ultrasonic cleaning; the time of the ethanol ultrasonic cleaning is 0.5 to 24 hours; The drying temperature is 50-120°C and the drying time is 1-24h; The inert atmosphere is at least one of argon, nitrogen, helium and carbon monoxide; The high temperature carbonization temperature is 500-1800° C., the time is 1-10 hours, and the heating rate is 1-20° C. / min.

[0015] Preferably, in step (3), the alkali solution is an aqueous solution of alkali, and the alkali is at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide, and ammonia water; the molar concentration of the alkali solution is 0.1-10 mol / L; the temperature of the alkali solution washing is 30-90°C, and the time is 0.5-12 hours; preferably, the molar concentration of the alkali solution is 3-7 mol / L, the temperature of the alkali solution washing is 60-90°C, and the time is 5-12 hours.

[0016] Preferably, in step (3), the acid solution is an aqueous solution of an acid, and the acid is at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, carbonic acid, and hydrofluoric acid; the molar concentration of the acid solution is 0.1 to 10 mol / L; the temperature of the acid solution washing is 30 to 80°C, and the time is 0.5 to 12 hours; preferably, the concentration of the acid solution is 2 to 4 mol / L, the temperature of the acid solution washing is 50 to 70°C, and the time is 5 to 12 hours.

[0017] Preferably, in step (3), the drying temperature is 50 to 120° C. and the drying time is 1 to 24 hours.

[0018] Preferably, the particle size of the vascular plant derived carbon sodium ion negative electrode material is 0 to 75 μm, preferably 5 to 20 μm.

[0019] The part of the plant vascular bundle selected by the present invention where the distribution is relatively dense has a relatively high cellulose content, which is conducive to the formation of closed micropores in the hard carbon and increases the sodium storage capacity. The pores formed by the carbonization of the vascular bundle are conducive to the transmission of sodium ions. Washing with alkaline solution and acid solution can effectively remove the ash after the carbonization of the biomass, especially the silicon dioxide that exists in large quantities in the silicon cells of the plant epidermis, and reduce the adverse effects of inactive substances and trace elements on battery performance. After washing, the vascular bundle-derived carbon with a certain structural strength is crushed to a certain particle size to obtain a vascular plant-derived carbon sodium ion battery negative electrode material.

[0020] The plant vascular tissue selected by the present invention is widely present in the leaf and stem epidermis of monocotyledonous plants or the xylem and phloem of the secondary growth of the root and stem of dicotyledonous plants, so the selection of biomass precursor materials is very wide. The vascular bundles are interconnected to form a vascular system, the main function of which is to transport water, inorganic salts and organic nutrients to the plant body, and also has the function of supporting the plant body.

[0021] The present invention uses biological tissues rich in vascular bundles as hard template precursor materials. At an appropriate temperature, cellulose, lignin, etc. inside the biomass are graphitized to form a hard carbon network, while being able to inherit the directional pore framework of the vascular bundle with greater rigidity.

[0022] The vascular biomass hard carbon studied in the present invention is conducive to the full infiltration of the electrolyte, while reducing the diffusion impedance and transmission distance of sodium ions, providing a "highway" for the migration of sodium ions in the hard carbon network, and can significantly improve the rate performance of the hard carbon material.

[0023] Beneficial effects: (1) The raw materials used in the present invention are easy to obtain and widely distributed, the processing process is simple and easy to operate, and the carbonization process is simple, which is easy to realize industrialization. (2) The biomass portion with densely distributed vascular bundles selected by the present invention has a high cellulose content, which is conducive to the formation of closed micropores in hard carbon and improves the sodium storage capacity. The high cellulose content enables its first coulombic efficiency to reach 70-90%. The micropores / nanopores naturally formed by the carbonization of the vascular bundle structure are conducive to the transmission of sodium ions inside the hard carbon and have a higher rate performance. (3) The constant temperature alkali washing and acid washing steps in the present invention can effectively remove the ash in the biomass carbon, especially the high temperature alkali washing can effectively remove the silicon dioxide component in the epidermal silicon cells of monocotyledonous plants, reduce the mass ratio of inactive substances in the vascular bundle derived carbon that do not exert the sodium storage performance, and the vascular bundle derived carbon sodium ion battery negative electrode material has a high performance of 25mAh·g -1 The current density is as high as 290 mAh g -1 reversible sodium storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the vascular bundle-derived carbon sodium ion battery negative electrode material in Example 1; Figure 2 The X-ray diffraction pattern of the vascular bundle derived carbon sodium ion battery negative electrode material in Example 1; Figure 3 The first two charge and discharge curves of the vascular bundle-derived carbon sodium ion battery in Example 1; Figure 4 This is the cycle curve of the vascular bundle derived carbon sodium ion battery in Example 1. DETAILED DESCRIPTION

[0025] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0026] In the present invention, the vascular bundle-derived carbon sodium ion negative electrode material has micropores / nanopores formed by carbonization of the epidermal biomass structure, the pore size of the micropores is between 1 and 10 μm, and the pore size of the nanopores is between 0.1 and 10 nm. The advantages of the micropores / nanopores generated by the present invention are uniform distribution, moderate size, and parallel array straight-through channels, which are conducive to the infiltration of electrolytes and the efficient transmission of sodium ions. The vascular bundle-derived carbon sodium ion negative electrode material is used as a negative electrode material for sodium ion batteries. At 25 mAg -1 The current density is as high as 290 mAh g -1 The reversible capacity is 70% to 90% for the first coulombic efficiency.

[0027] The present invention provides a method for processing tissues with densely distributed vascular bundles in plants to obtain vascular bundle-derived carbon sodium ion negative electrode materials with high specific capacity and high first coulomb efficiency. The method can relatively easily remove ash from biomass, especially silicon dioxide with a high content in the epidermis.

[0028] The present invention uses vascular plant tissue as a hard template. At high temperature, the cellulose, lignin and other components in the precursor will be graphitized to form hard carbon. At the same time, the parallel straight channels of the natural vascular structure will be retained, which is conducive to the infiltration of electrolytes and the migration and diffusion of sodium ions in the hard carbon.

[0029] The following is an exemplary description of the method for preparing the vascular plant derived carbon sodium ion battery negative electrode material provided by the present invention.

[0030] Preparation of biomass precursor: Take the part of the plant with dense vascular bundles and peel off the part with less vascular bundles to obtain the biomass precursor. Specifically, pick the plant and remove the spongy trunk and mesophyll with less internal vascular tissue, leaving the epidermis, roots, xylem and phloem rich in vascular tissue.

[0031] In an optional embodiment, the densely distributed part of the plant vascular bundle is the leaf and stem epidermis of monocotyledonous plants or the xylem and phloem of secondary growth of roots and stems of dicotyledonous plants; the monocotyledonous plants are at least one of wheat, corn, ginger flower, rice, leek, onion, daylily, cucumber, garlic, lily, sugarcane, bamboo, orchid, iris, palm tree and cattail; the dicotyledonous plants are at least one of cotton, soybean, peanut, sunflower, sweet potato, potato, apple, tobacco, mint and various melons; preferably, the densely distributed part of the plant vascular bundle is the epidermis of fully mature cattail leaves, the green bamboo part of bamboo or the bark part of gymnosperm (ginkgo). The reason for selecting the densely distributed part of the plant vascular bundle in the present invention is that the hard carbon network and the parallel array straight-through pore structure of the vascular bundle can be obtained at the same time.

[0032] Preparation of vascular plant derived carbon: The obtained biomass precursor is cleaned and dried, and then placed in an inert atmosphere for high temperature carbonization to obtain vascular plant derived carbon.

[0033] In an optional embodiment, the cleaning includes deionized water cleaning and ethanol ultrasonic cleaning, wherein the deionized water cleaning is to remove dirt on the surface of the precursor. The ethanol ultrasonic cleaning includes: placing the water-washed precursor in a container, adding ethanol, and ultrasonically cleaning in an ultrasonic device for 0.5 to 24 hours.

[0034] The drying temperature is 50-120° C. and the drying time is 1-24 hours.

[0035] The inert atmosphere is at least one of argon, nitrogen, helium and carbon monoxide.

[0036] The temperature of the high-temperature carbonization is 500-1800°C, the time is 1-10 hours, and the heating rate is 1-20°C / min. The role of the high-temperature carbonization of the present invention is to use the natural cellulose and lignin inside the biomass as carbon sources to obtain hard carbon materials. If the temperature of the high-temperature carbonization is too high, the degree of graphitization of the hard carbon will be too high, resulting in a smaller carbon layer spacing, which is not conducive to the intercalation storage of sodium ions; if the temperature is too low, it is not conducive to the removal of impurities, and if the degree of graphitization of the biomass is too small, the conductivity of the carbon material will be reduced, which is not conducive to the transmission of charges or charges in the straight through channels of the parallel array. If the time of the high-temperature carbonization is too long, it will cause excessive energy consumption; if the time is too short, it will be not conducive to the rearrangement of internal carbon atoms and the formation of hard carbon materials.

[0037] Preparation of vascular plant derived carbon sodium ion negative electrode material: washing the vascular plant derived carbon with alkaline solution, acid solution and deionized water respectively, and then drying, grinding and sieving to obtain the vascular plant derived carbon sodium ion negative electrode material.

[0038] In an optional embodiment, the steps of washing with alkali solution and acid solution include: placing the carbonized vascular bundle derived carbon in a beaker, adding alkali solution, washing with constant temperature stirring, then washing the residual alkali solution with deionized water, adding acid solution, washing with constant temperature stirring, and then washing the vascular bundle derived carbon material with deionized water; wherein the linear speed of stirring is 0.5 to 3 m / s. The purpose of the alkali solution washing of the present invention is to remove silicon cells inside the herbaceous plant. The purpose of the acid solution washing is to remove ash and impurities in the hard carbon material.

[0039] The alkali solution is an aqueous solution of alkali, and the alkali is at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide, and ammonia water. The molar concentration of the alkali solution is 0.1-10 mol / L; if the molar concentration of the alkali solution is too high, the danger of the experimental process will increase, and if it is too low, the purpose of removing silicon cells inside the plant will not be achieved. The temperature of the alkali solution washing is 30-90°C, and the time is 0.5-12 hours; preferably, the molar concentration of the alkali solution is 3-7 mol / L, the temperature of the alkali solution washing is 60-90°C, and the time is 5-12 hours; the present invention can accelerate the removal process of silicon cells by hot alkali solution washing. If the temperature of the alkali solution washing is too high, the danger of the experimental process will increase; if the temperature is too low, it will be difficult to remove silicon cells. If the time of the alkali solution washing is too long, unnecessary energy consumption will be caused; if the time is too short, the purpose of removing silicon cells inside the plant will not be achieved.

[0040] The acid solution is an aqueous solution of acid, and the acid is at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, carbonic acid, and hydrofluoric acid; the molar concentration of the acid solution is 0.1-10 mol / L; the temperature of the acid solution washing is 30-80°C, and the time is 0.5-12 hours; preferably, the concentration of the acid solution is 2-4 mol / L, the temperature of the acid solution washing is 50-70°C, and the time is 5-12 hours. If the acid solution concentration is too low, the purpose of removing ash and impurities will not be achieved; if the acid solution concentration is too high, it will not only increase the risk of the experiment, but also make the metal nanoparticles or metal oxides passivated and difficult to remove; if the washing temperature is too high, it will cause unnecessary energy consumption; if the temperature is too low, the purpose of removing ash and impurities will not be achieved. If the acid solution washing time is too long, it will cause unnecessary energy consumption; if the time is too short, the purpose of removing ash and impurities will not be achieved.

[0041] The deionized water washing step comprises: immersing the vascular bundle derived carbon in deionized water, ultrasonically cleaning for 0.1 to 2 hours, filtering, and repeating 3 to 8 times.

[0042] The drying temperature is 50-120° C. and the drying time is 1-24 hours.

[0043] The particle size of the vascular plant derived carbon sodium ion negative electrode material after screening is 0 to 75 μm, preferably 5 to 20 μm.

[0044] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0045] Example 1 (1) taking fully mature cattail leaves, peeling off the spongy tissue of the mesophyll part, retaining the cattail leaf epidermis with densely distributed vascular bundles, and taking 10 g of the cattail leaf epidermis as a precursor; (2) The epidermis of cattail leaves was cleaned with deionized water, placed in a beaker, and 100 mL of ethanol was added for ultrasonic treatment for 2 h. The cleaned sample was placed in a 60°C blast oven for drying for 12 h; the dried cattail leaf epidermis was placed in a corundum crucible and carbonized in a tube furnace under an argon atmosphere, and the temperature was increased to 1200°C at a heating rate of 5°C / min, and the temperature was kept for 3 hours. After natural cooling, the cattail carbon sample was taken out; (3) The cattail carbon sample was washed with alkali solution, acid solution and deionized water respectively, dried in a 90°C forced air oven for 12 h, ground and sieved to obtain a sample with a mesh size of 600 to 3000, which is the cattail vascular bundle derived carbon sodium ion battery negative electrode hard carbon material; The alkali washing step is as follows: take 70.13g of potassium hydroxide, use a 250mL volumetric flask, and prepare a 5M KOH aqueous solution with potassium hydroxide and deionized water. Take 50mL of the prepared alkali solution in a beaker, add cattail carbon, and stir magnetically at 90°C for 12h at a speed of 200rpm. After this step is completed, filter to remove the alkali solution, and wash away the residual alkali solution with deionized water; The pickling step is as follows: take 75.06g of 98% concentrated sulfuric acid, use a 250mL volumetric flask, and prepare a 3M sulfuric acid solution with concentrated sulfuric acid and deionized water. Take 50mL of the prepared acid solution in a beaker, add the alkali-washed cattail carbon, and stir magnetically for 12h at 60°C and 200rpm. After this step is completed, filter to remove the acid solution, and wash the residual acid solution with deionized water.

[0046] Battery performance test: The negative electrode material of the cattail vascular bundle-derived carbon sodium ion battery, conductive carbon black and sodium carboxymethyl cellulose were mixed in a ratio of 8:1:1 with deionized water as the solvent to prepare the battery negative electrode slurry, which was coated on an aluminum foil with a thickness of 10μm. After vacuum drying at 80°C for 10 hours, it was cut into discs with a diameter of 12mm. Using a metal sodium sheet as the counter electrode, a whatman glass fiber membrane as the diaphragm, and a solution of diethylene glycol dimethyl ether dissolved with NaPF6 (1mol / L) as the electrolyte, a CR2032 battery was assembled in an argon-protected glove box. After the battery was assembled, it was left to stand for 8 hours, and then a constant current charge and discharge test was performed using the Blue Electric CT2001A battery test system. The test voltage was 0.01~2V, and the current density was 25mA·g in the first three cycles. -1 After three charge and discharge cycles, the current density is 100 mA g -1 .

[0047] Figure 1 This is a scanning electron microscope image of the vascular bundle-derived carbon sodium ion battery negative electrode material in Example 1. As can be seen from the figure, the obtained hard carbon material inherits the parallel array straight channel structure of the vascular bundle, which can promote the infiltration of the electrolyte and provide a "highway" for the migration of sodium ions inside.

[0048] Figure 2 This is the X-ray diffraction spectrum of the vascular bundle-derived carbon sodium-ion battery negative electrode material in Example 1. It can be seen from the figure that two characteristic diffusion peaks of amorphous carbon appear.

[0049] Figure 3 The charge-discharge curves of the first two cycles of the vascular bundle-derived carbon sodium ion battery in Example 1 show that the negative electrode material of the vascular bundle-derived carbon sodium ion battery has a capacity of up to 290 mAh·g -1 reversible capacity.

[0050] Figure 4 1 is the cycle curve of the vascular bundle derived carbon sodium ion battery in Example 1. As can be seen from the figure, at 100 mA·g -1 At a current density of 2.5 Å, the vascular-derived carbon exhibited good sodium storage performance with a reversible capacity of up to 270 mAh g -1 At the same time, the hard carbon material has excellent stability. After 100 discharge-charge cycles, the reversible capacity is still 255 mAh g -1 , the capacity retention rate reached 94.4%.

[0051] Example 2

[0052] The preparation process of the vascular plant-derived carbon sodium ion battery negative electrode material in this embodiment 2 refers to that in embodiment 1, except that the precursor material is the green part of mature bamboo, and the preparation method is as follows: (1) Take mature bamboo and select 10 g of the green part of the bamboo (where vascular bundles are most abundant and cellulose content is high) as a precursor; (2) Wash the bamboo green with deionized water, put it in a beaker, add 100 mL of ethanol and ultrasonicate for 2 h, and dry the cleaned sample in a 60°C blast oven for 12 h; put the dried bamboo green into a corundum crucible, and carbonize it in a tube furnace under an argon atmosphere, heating it to 1000°C at a heating rate of 5°C / min, keep it warm for 3 hours, and take out the bamboo green carbon sample after natural cooling; (3) The bamboo green carbon sample was washed with alkali solution, acid solution and deionized water respectively, and then dried in a 90°C forced air oven for 12 h. After grinding and sieving, a sample with a mesh size of 600 to 3000 was obtained, which was the bamboo green vascular bundle derived carbon sodium ion battery negative electrode hard carbon material; The alkali washing step is as follows: take 70.13g of potassium hydroxide, use a 250mL volumetric flask, and prepare a 5M KOH aqueous solution with potassium hydroxide and deionized water. Take 50mL of the prepared alkali solution in a beaker, add bamboo green carbon, and stir magnetically at 60°C for 12h at a speed of 200rpm. After this step is completed, filter to remove the alkali solution, and wash the residual alkali solution with deionized water; The pickling step is as follows: take 75.06g of 98% concentrated sulfuric acid, use a 250mL volumetric flask, and prepare a 3M sulfuric acid solution with concentrated sulfuric acid and deionized water. Take 50mL of the prepared acid solution in a beaker, add the alkali-washed bamboo green carbon, and stir magnetically for 12h at 60°C and 200rpm. After this step is completed, filter to remove the acid solution, and wash the residual acid solution with deionized water.

[0053] Example 3

[0054] The preparation process of the vascular plant-derived carbon sodium ion battery negative electrode material in this embodiment 3 refers to that in embodiment 1, except that: the precursor material is the outer layer tissue of the ginkgo trunk, and the preparation method is as follows: (1) Take the outer 2 cm thick tissue of the trunk of a ginkgo tree (including bark and vascular tissue), peel off the outermost bark (i.e., epidermis, cortex, and cork layer), and take 10 g of the vascular cambium as a precursor; (2) The precursor was washed with deionized water, placed in a beaker, and 100 mL of ethanol was added for ultrasonic treatment for 2 h. The washed sample was placed in a 120° C. forced air oven for drying for 12 h. The dried precursor was placed in a corundum crucible and carbonized in a tube furnace under an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min, and the temperature was kept for 3 h. After natural cooling, the water hyacinth-derived carbon was taken out. (3) The water hyacinth derived carbon sample was washed with alkali solution, acid solution and deionized water respectively, and then dried in a 90°C forced air oven for 12 h. After grinding and sieving, a sample with a mesh size of 600 to 3000 was obtained, which is the water hyacinth vascular bundle derived carbon sodium ion battery negative electrode hard carbon material; The alkali washing step is as follows: take 42.08g of potassium hydroxide, use a 250mL volumetric flask, and prepare a 3M KOH aqueous solution with potassium hydroxide and deionized water. Take 50mL of the prepared alkali solution in a beaker, add water hyacinth derived carbon, and stir magnetically for 3h at 60°C and 200rpm. After this step is completed, filter to remove the alkali solution, and wash away the residual alkali solution with deionized water; The pickling step is as follows: take 25.02g of 98% concentrated sulfuric acid, use a 250mL volumetric flask, and prepare a 1M sulfuric acid solution with concentrated sulfuric acid and deionized water. Take 50mL of the prepared acid solution in a beaker, add the water hyacinth derived carbon after alkali washing, and stir magnetically for 3h at 60°C and 200rpm. After this step is completed, filter to remove the acid solution, and wash the residual acid solution with deionized water. Dry the washed sample in a 90°C blast oven for 12h.

[0055] Comparative Example 1

[0056] The difference between Comparative Example 1 and Example 1 is that the precursor material is not subjected to an alkaline washing step.

[0057] Comparative Example 2

[0058] The difference between Comparative Example 2 and Example 1 is that the concentration of alkali in the alkali washing step of the precursor material is 0.05 mol / L.

[0059] Comparative Example 3

[0060] The difference between Comparative Example 3 and Example 1 is that the concentration of the acid solution in the precursor material pickling step is 12 mol / L.

[0061] Comparative Example 4

[0062] The difference between Comparative Example 4 and Example 1 is that in step (2), the temperature of heat treatment of the precursor material is 300°C.

[0063] The carbon materials prepared in Examples 2-3 and Comparative Examples 1-4 were subjected to electrochemical tests. The electrochemical test process was carried out at 100 mA·g -1 The assembled battery was placed for 8 hours and then charged and discharged at a current density of 25 mA g -1 The battery was discharged to 0.01V with a constant current, left for 5 minutes, and then charged to 2.0V with the same constant current, and left for another 5 minutes. The above process was repeated 3 times to activate the battery. -1The constant current charge and discharge cycle was carried out with a current of 0.01-2.0 V. The sodium storage performance of the obtained carbon material is shown in Table 1.

[0064] Table 1:

[0065] It can be seen from Table 1 that the carbon materials prepared in Examples 2-3 and Comparative Examples 1-4 have obvious differences in sodium storage performance. The reason is that the source of the precursor and the alkaline and acid washing processes play a decisive role in the sodium storage specific capacity, the first-cycle coulomb efficiency and the cycle stability. The precursor material selected in the present invention has a rich vascular bundle structure, and the hard carbon obtained after heat treatment can well inherit the parallel array through-hole structure of the vascular bundle, which can effectively promote the migration of sodium ions. The alkaline and acid washing processes can effectively remove impurities and ash from the precursor material or after carbonization, and reduce the influence of inactive substances on the sodium storage performance of the hard carbon material. At the same time, a suitable heat treatment process can accurately control the degree of graphitization and the microstructure of the negative electrode material.

Claims

1. A vascular plant derived carbon sodium ion battery negative electrode material, characterized in that: The vascular plant derived carbon sodium ion battery negative electrode material is generated by carbonization of tissues with densely distributed plant vascular bundles; the vascular plant derived carbon sodium ion negative electrode material has micropores or nanopores.

2. The vascular plant derived carbon sodium ion battery negative electrode material according to claim 1, characterized in that: The diameter of the micropore is 1-10 μm; the diameter of the nanopore is 0.1-10 nm.

3. The vascular plant derived carbon sodium ion battery negative electrode material according to claim 1 or 2, characterized in that: The vascular plant derived carbon sodium ion negative electrode material has a high conductivity at 25 mAg -1 The current density is 250~400mAh g -1 The reversible capacity of the battery is 70% to 90% for the first time.

4. A method for preparing a negative electrode material for a vascular plant-derived carbon sodium ion battery as claimed in claims 1 to 3, characterized in that: include: (1) taking a part of the plant where vascular bundles are densely distributed, and peeling off a part where vascular bundles are less distributed, to obtain a biomass precursor; (2) washing and drying the obtained biomass precursor and then carbonizing it at high temperature in an inert atmosphere to obtain vascular plant-derived carbon; (3) The vascular plant-derived carbon is washed with alkaline solution, acid solution and deionized water respectively, and then dried, ground and sieved to obtain the vascular plant-derived carbon sodium ion negative electrode material.

5. The preparation method according to claim 4, characterized in that: In step (1), the part where the plant vascular bundles are densely distributed is the epidermis of leaves and stems of monocotyledons or the xylem and phloem of secondary growth of roots and stems of dicotyledons; the monocotyledons are at least one of wheat, corn, ginger flower, rice, leek, onion, daylily, cucumber, garlic, lily, sugarcane, bamboo, orchid, iris, palm tree and cattail; the dicotyledons are at least one of cotton, soybean, peanut, sunflower, sweet potato, potato, apple, tobacco, mint and various melons; preferably, the part where the plant vascular bundles are densely distributed is the epidermis of fully mature cattail leaves, the green part of bamboo or the bark of gymnosperms.

6. The preparation method according to claim 4 or 5, characterized in that: In step (2), the cleaning includes deionized water cleaning and ethanol ultrasonic cleaning, and the time of the ethanol ultrasonic cleaning is 0.5 to 24 hours; The drying temperature is 50-120°C and the drying time is 1-24h; The inert atmosphere is at least one of argon, nitrogen, helium and carbon monoxide; The high temperature carbonization temperature is 500-1800° C., the time is 1-10 hours, and the heating rate is 1-20° C. / min.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (3), the alkali solution is an aqueous solution of alkali, and the alkali is at least one of potassium hydroxide, sodium hydroxide, and lithium hydroxide; the molar concentration of the alkali solution is 0.1 to 10 mol / L; the temperature of the alkali solution washing is 30 to 90° C., and the time is 0.5 to 12 hours; preferably, the molar concentration of the alkali solution is 3 to 7 mol / L; the temperature of the alkali solution washing is 60 to 90° C., and the time is 5 to 12 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (3), the acid solution is an aqueous solution of an acid, and the acid is at least one of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, and carbonic acid; the molar concentration of the acid solution is 0.1 to 10 mol / L; the temperature of the acid solution washing is 30 to 80° C., and the time is 0.5 to 12 hours; preferably, the concentration of the acid solution is 2 to 4 mol / L; the temperature of the acid solution washing is 50 to 70° C., and the time is 5 to 12 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (3), the drying temperature is 50 to 120° C. and the drying time is 1 to 24 hours.

10. The preparation method according to any one of claims 4 to 9, characterized in that: In step (3), the particle size of the vascular plant derived carbon sodium ion negative electrode material is 0 to 75 μm, preferably 5 to 20 μm.

Citation Information

Patent Citations

  • Waste biomass kernel derived hard carbon material as well as preparation method and application thereof

    CN115863634A